Etika Profesi Konselor dalam Pelaksanaan Layanan Bimbingan Konseling di Dunia Internet - Akhir Pardamean; Agus Salim Nst; Riski Indah Sari; Taufiq Ismail Koto (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The aim of this research is to provide an explanation of the professional standards required by counselors when they provide counseling guidance services via the internet. This research investigates the literature through a qualitative descriptive approach. The data comes from previous research and document studies from various references. Descriptive analysis is the next data analysis method used. The research results show that online counseling is a counseling technology in cyberspace or virtual worlds, such as computers, video conferencing, instant messaging, chat, websites, telephone or email, and other social networks. Building good relationships on the Internet, maintaining confidentiality when conducting consultations, licensing, and legal aspects of telecommunications via the Internet are ethics that must be adhered to by online counselors. Therefore, online counselors must be experienced in providing virtual counseling with consideration